Discolouring Democracy? Policing, Sensitive Evidence, and Contentious Deaths in the United Kingdom. (November 2013) - Martin, Greg; Bray, Rebecca Scott
Abstract : This article examines recent United Kingdom government proposals for secret inquests, which, it is argued, are part of a general push for secrecy discernible across common law jurisdictions, and which include developments such as increased recourse to sensitive evidence in forensic settings and the normalization of intelligence‐led policing. While the push for secrecy is justified by national security claims, the article shows that in cases of contentious death involving police, the issue is less about national security and more about the use of intercept evidence, covert surveillance, and intelligence‐led policing, all of which have implications for police trust, accountability, and reputation management.